Tajikistan : Higher Education Sector Study - World Bank (Washington, DC, 2015)
The introduction provides background on higher education reforms in Tajikistan and the rationale for this study. Chapter one presents an overview of the higher education system. Chapter two outlines the system-wide governance framework for Tajikistan s higher education system. It examines the regulatory framework governing higher education, system-level and institutional-level governance, stakeholders participation, and corruption. Chapter three reviews international trends in quality assurance as a benchmark for Tajikistan and examines Tajikistan s existing quality assurance system. Chapter four analyzes the higher education financing model in Tajikistan. Chapter five assesses the feasibility of using Information and Communication Technologies to improve access, quality, and relevance of higher education in Tajikistan. It also presents the results of an innovative pilot project to apply ICT-based solutions for higher education challenges. Chapter six concludes with a summary of findings and policy recommendations.